Destruction of the multicellular parasite Schistosoma mansoni by T lymphocytes. - Ellner, J J (1982)
The role of cytotoxic T lymphocytes in host defenses against infectious agents is unknown as these cells have not previously been demonstrated to kill microorganisms directly. We studied the cytotoxicity of T lymphocytes purified from peripheral blood mononuclear cells of healthy subjects for the multicellular schistosomula of Schistosoma mansoni. Unstimulated and phytohemagglutinin (PHA)-stimulated T cells were cultured with schistosomula at a 5,000:1 effector/target (E:T) ratio for 18 h at 37 degrees C. Unstimulated T cells killed 2.1 +/- 0.6% of schistosomula as judged by dye uptake and did not change their infectivity for mice. In contrast, PHA-stimulated T cells killed 41.3 +/- 3.1% of schistosomula by dye uptake and 56.7 +/- 7.7% of these organisms could not mature to adult worms in vivo. Killing was associated with and dependent on increased binding of PHA-stimulated T lymphocytes to schistosomula. Significant schistosomula killing first was noted after 2 h of exposure to T cells to PHA and peaked at 24; enhanced killing by PHA-stimulated cells was observed at an E:T ratio of 500:1 and was maximal at 5,000:1. Exposure of T lymphocytes to oxidative mitogens, soluble antigens, and alloantigens also resulted in enhanced killing of schistomula. These studies show that T lymphocytes activated by a variety of stimuli develop the capacity to kill schistosomula of Schistoma mansoni. Direct killing of infectious agents by cytotoxic T cells may contribute to host resistance to infections.